An atypical R2R3 MYB transcription factor increases cold hardiness by CBF-dependent and CBF-independent pathways in apple - Xie, Yinpeng (The New phytologist, 2018)
© 2017 Northwest A&F University New Phytologist © 2017 New Phytologist Trust.